2008
DOI: 10.1128/aac.00673-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Artesunate Administration and Cytochrome P4502C8 Polymorphisms on the Pharmacokinetics of Amodiaquine in Ghanaian Children with Uncomplicated Malaria

Abstract: Artesunate (AS) is used in combination with amodiaquine (AQ) as first-line treatment for uncomplicated malaria in many countries. We investigated the effect of concomitant AS administration on the pharmacokinetics of AQ and compared concentrations of desethylamodiaquine (DEAQ), the main metabolite of AQ, in plasma between patients with different variants of the cytochrome P4502C8 (CYP2C8) gene. A two-compartment model was fitted to 169 plasma DEAQ concentrations from 103 Ghanaian children aged 1 to 14 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…Three previous studies have described the pharmacokinetic properties of amodiaquine and desethylamodiaquine in nonpregnant adults and children using nonlinear mixed-effects modeling (2,17,23). A nonlinear mixed-effects approach, in contrast to results from a noncompartmental analysis, provides a mechanistic understanding of the pharmacokinetic properties of the drug with the ability to characterize potential covariate relationships with higher statistical power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three previous studies have described the pharmacokinetic properties of amodiaquine and desethylamodiaquine in nonpregnant adults and children using nonlinear mixed-effects modeling (2,17,23). A nonlinear mixed-effects approach, in contrast to results from a noncompartmental analysis, provides a mechanistic understanding of the pharmacokinetic properties of the drug with the ability to characterize potential covariate relationships with higher statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Interindividual random variability in all parameters was modeled exponentially: i ϭ ϫ exp( i, ), where i is the individually estimated parameter value for the ith patient, is the typical parameter value for the modeled population, and i, is the interindividual random variability assumed to be normally distributed with a zero mean and variance 2 . Correlations between variability components were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in eastern Africa, where malaria is ranked second in terms of its contribution to DALYs, only two countries have been investigated. In western Africa, where malaria is the highest contributor to disease burden, three countries have allelic frequency data for CYP2C8, namely Burkina Faso [34,35], Ghana [36][37][38] and…”
Section: Cyp2c8 and The Management Of Malariamentioning
confidence: 99%
“…Studies in Burkina Faso and Ghana have not revealed a relationship between drug efficacy and CYP2C8 genotype. 30,31 While the percentage of the population with an inactivating CYP2C8 genetic variant is not high in most malaria-endemic regions, the overall incidence of risk is significant due to the burden of disease. For example, Cavaco et al estimated that the CYP2C8*2 and CYP2C8*3 genetic variants occur in 2.1% of the population in Zanzibar, United Republic of Tanzania: this translates into more than 30 000 patients per year at risk for severe drug reactions to amodiaquine (of a malaria patient population of ~1 000 000).…”
Section: The Case Of Amodiaquinementioning
confidence: 99%